Faktor-Faktor yang Berhubungan Dengan Kejadian Proteinuria pada Pasien Diabetes Melitus di Puskesmas I dan IV Denpasar Selatan - PUTU ARYA SURYANDITHA; NI MADE DHANISWARA PUTRI WIRAWAN; DEWA AYU PUTRI SRI MASYENI (HANG TUAH MEDICAL JOURNAL, 2022)
Diabetes Mellitus (DM) is a major health problem in the world. Various complications can arise due to uncontrolled blood sugar levels. One of the complications of DM involving the kidneys is diabetic nephropathy, which is characterized by the occurrence of proteinuria in DM patients. This study aims to determine the factors associated with the incidence of proteinuria in patients with diabetes mellitus at Puskesmas I and IV Denpasar Selatan. The design in this study is an analytical study with a cross sectional approach using primary data obtained from interviews and urinalysis examinations. The minimum sample size in this study was 106 people who met the inclusion and exclusion criteria. Data were analyzed using Chi Square test with a significance level of 5%. The number of respondents in this study were 106 respondents. The results of this study showed that as many as 33% of all DM patients had proteinuria. There is a significant relationship between the onset of DM and the incidence of proteinuria (p<0.05), so it can be interpreted that the longer the duration of experiencing DM, the incidence of proteinuria will increase, and vice versa. There was no significant relationship between age, gender, BMI, type of DM therapy, and fasting blood glucose levels with the incidence of proteinuria (p>0,05). Patients with diabetes onset more than 10 years tend to have proteinuria. DM patients are advised to do regular proteinuria checks if the onset of DM is more than 5 years.